Exiting the extraordinary : returning to the ordinary world after war, prison, and other extraordinary experiences - Moulder, Frances V. (Frances Valentine), 1945- (Lexington Books, 2016)
This book is a sociological exploration of the process of returning to the ordinary world after extraordinary experiences. It provides many lively examples, both contemporary and historical, of the commonalities among extraordinary experiences, the challenges faced by returnees, strategies returnees follow in dealing with these challenges, and public policy changes needed to support the return process.